2008
DOI: 10.1002/pmic.200700942
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic response to iron deficiency in tomato root

Abstract: To know the root adjustment in response to iron deficiency, differentially displayed proteins in tomato roots of wild type and its iron uptake inefficient mutant T3238fer were analyzed by 2-DE and MALDI-TOF MS-based proteomic method under iron sufficiency and deficiency. Ninety-seven proteins were identified, 63 of them were classified in various metabolic pathways. About 40 proteins involved in starch degradation, TCA and ascorbate cycles were upregulated under iron deficiency and grouped in a network togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
69
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 45 publications
16
69
4
1
Order By: Relevance
“…In support of previous studies at the protein or transcript level, glycolysis appears to be activated upon Fe deficiency (Thimm et al, 2001;Brumbarova et al, 2008;Li et al, 2008Li et al, , 2009Rellán-Alvarez et al, 2010). The data from this study support this finding and add several novel aspects regarding changes of carbon flow during Fe deficiency.…”
Section: Phosphoproteomics Reveals Novel Aspects In Carbohydrate Metasupporting
confidence: 80%
“…In support of previous studies at the protein or transcript level, glycolysis appears to be activated upon Fe deficiency (Thimm et al, 2001;Brumbarova et al, 2008;Li et al, 2008Li et al, , 2009Rellán-Alvarez et al, 2010). The data from this study support this finding and add several novel aspects regarding changes of carbon flow during Fe deficiency.…”
Section: Phosphoproteomics Reveals Novel Aspects In Carbohydrate Metasupporting
confidence: 80%
“…SAM is synthesized from L-Met by S-Met adenosyltransferase (MAT). SAM synthetases are massively up-regulated at the protein level upon Fe starvation, in accordance with previous proteomic studies in tomato (Solanum lycopersicum), cucumber, and Chlamydomonas (Reinhardt et al, 2006;Li et al, 2008;Li and Schmidt, 2010). The protein abundance of three out of four Arabidopsis MAT isoenzymes, MAT1, MAT2, and MAT3, was increased by Fe deficiency.…”
Section: Sam Is a Central Metabolite In Fe-deficient Rootssupporting
confidence: 71%
“…When we compared the responses in C. reinhardtii to those documented in Arabidopsis, tomato (Solanum lycopersicum), and rice, transporters and antioxidant proteins were well represented as well, indicative of the importance of these processes throughout the plant lineage. In fact, several studies have demonstrated that iron deficiency results in enhanced antioxidant mechanisms in plants, algae, and diatoms (Zaharieva and Abadía, 2003;Allen et al, 2008;Li et al, 2008;Thamatrakoln et al, 2012). …”
Section: Conserved Responses To Poor Iron Nutritionmentioning
confidence: 99%